The Naturalism and Historical Biographical Reconstruction - Agustin, Nini (Yayasan Sembilan Pemuda Indonesia, 2024)
According to naturalism, only natural laws and forces apply in the universe, not supernatural forces. The aim of this article is to see how Abu Bakar Alrazi's theistic naturalistic reasoning developed using the method of historical biographical reconstruction. This allows us to understand and explore a person's personality through a sociocultural and intellectual lens. This study produces several conclusions. First, as a scientist, Alrazi used theistic naturalistic reasoning because the social and religious conditions of his time manipulated truth and limited the potential of reason. In addition, religious communities are prohibited from rational speculation about religion because religion is considered sacred and well-established. This is the reason why truth is secretive and secretive in nature, according to Alrazi. Second, Alrazi, who believes in pure rationalism, considers reason as proof of the existence of God, because through reason humans can understand problems.